USING FAIRY TALES IN TEACHING ENGLISH TO YOUNG LEARNERS - D.B.Kayumov,; Xursanova Karina Timurovna, (TADQIQOTLAR, 2026)
Abstract This  article  explores  the  effectiveness  of  integrating  fairy  tales  into  English language instruction for young learners. It highlights the benefits of using familiar narratives  to  enhance  language  acquisition,  stimulate  imagination,  and  promote cultural understanding. The article discusses various strategies for incorporating fairy tales into lesson plans, such as storytelling, role-playing, and creative writing activities. Additionally, it addresses the cognitive and emotional development of children through engagement with these timeless stories. The article concludes with practical tips for educators  on  how  to  select  appropriate  fairy  tales  and  adapt  them  to  suit  different learning levels.